A Call for Policy Reform in COPD Management in Malaysia: Expert Opinions and Recommendations - Ahmad Izuanuddin Ismail; Nik Khairol Reza; Mohd Arif Mohd Zim; Mat Zuki Mat Jaeb; Mahani Kamaruddin; Jaya Muneswarao; Irfhan Ali Bin Hyder Ali; Ho Bee Kiau; Helmy Haja Mydin; Beni Isman Rusani; Arvindran Alaga; Pang Yong Kek (Journal of Clinical and Health Sciences, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a leading cause of morbidity and mortality in Malaysia, yet it remains under-recognised as a national health priority. This policy and practice review consolidates expert opinions from a multidisciplinary panel using structured surveys and face-to-face discussions. It proposes actionable strategies for the Malaysian government and other key stakeholders to address critical gaps in COPD care. The recommendations focus on boosting disease awareness, ensuring equitable access to diagnostic and treatment resources, and prioritising COPD as a major non-communicable disease. Effective implementation of these recommendations could significantly improve patient outcomes and reduce disease burden nationwide.